The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41467-022-30517-y
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemically stable homogeneous glassy electrolyte formed at room temperature for all-solid-state sodium batteries

Abstract: All-solid-state sodium batteries (ASSSBs) are promising candidates for grid-scale energy storage. However, there are no commercialized ASSSBs yet, in part due to the lack of a low-cost, simple-to-fabricate solid electrolyte (SE) with electrochemical stability towards Na metal. In this work, we report a family of oxysulfide glass SEs (Na3PS4−xOx, where 0 < x ≤ 0.60) that not only exhibit the highest critical current density among all Na-ion conducting sulfide-based SEs, but also enable high-performance ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 65 publications
(50 reference statements)
5
95
0
Order By: Relevance
“…For example, in recent work in our group, we have shown how additions of O in the solid electrolyte (SE) Na 3 PS 4-x O x can not only create a SE that is stable in contact with metallic Na anodes, that the homogeneous structure of this SE produced by pressing also makes it resistant to Na metal dendrite penetration up to 1 mA/cm 2 current densities. 16 Similarly, Cengiz et al have shown that adding a source of oxygen, such as P 2 O 5 , to their Li 2 S−P 2 S 5 glass system improved the materials ability to suppress lithium metal (LM) dendrite formation and growth and thus improved the materials cycle life in a solid state lithium battery (SSLB). 26 Finally, it has long been known through the exhaustive work of Bates and Dudney et al that the incorporation of nitrogen into thin sputtered films of LiPON has also shown to advantageously improve the performance of GSEs, particularly the conductivity and electrochemical stability in contact with LM.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in recent work in our group, we have shown how additions of O in the solid electrolyte (SE) Na 3 PS 4-x O x can not only create a SE that is stable in contact with metallic Na anodes, that the homogeneous structure of this SE produced by pressing also makes it resistant to Na metal dendrite penetration up to 1 mA/cm 2 current densities. 16 Similarly, Cengiz et al have shown that adding a source of oxygen, such as P 2 O 5 , to their Li 2 S−P 2 S 5 glass system improved the materials ability to suppress lithium metal (LM) dendrite formation and growth and thus improved the materials cycle life in a solid state lithium battery (SSLB). 26 Finally, it has long been known through the exhaustive work of Bates and Dudney et al that the incorporation of nitrogen into thin sputtered films of LiPON has also shown to advantageously improve the performance of GSEs, particularly the conductivity and electrochemical stability in contact with LM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SSSBs, on the other hand, can be made from earth abundant low-cost materials, such as sodium and sulfur, and are much safer due their use of a solid-state inorganic electrolyte (SSIE). , In fact, sodium batteries (SBs) have already proven useful as grid-scale energy storage candidates through the application of oxide-based NASICON in ZEBRA batteries. However, their required high-operating temperatures of ∼300 °C to keep the NiCl 2 catholyte in the molten state creates a high energy penalty and a corrosive environment, which needs to be closely controlled . Sulfide-based Na 2 S–P 2 S 5 glasses and glass-ceramic materials, which have a conductivity of ∼10 –4 Ω-cm –1 at room temperature, have also been fabricated into SSSBs, but their pure sulfide chemistry and grain boundaries for the glass-ceramics create poor electrochemical stability and poor resistance to dendrite penetration, respectively. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li-ion batteries (LIBs) have expanded into application areas such as large-scale energy storage systems (ESSs) that could stabilize the power grid. , However, the price of Li rose more than 10-fold over the past decade (from 6.06 USD kg –1 in 2012 to 75 USD kg –1 in 2022 for Li 2 CO 3 ) . In addition, the uneven distribution of Li mines has caused political and economic issues. Moreover, there are safety concerns about LIBs, as seen from frequent fire accidents associated with the use of flammable organic liquid electrolytes. These factors have impeded the widespread use of LIBs for ESSs. ,, Solidifying electrolytes with nonflammable inorganic Na + superionic conductors could improve safety and reduce cost, making all-solid-state Na-ion or Na batteries (ASNBs) promising for use as ESSs. , …”
mentioning
confidence: 99%
“…Solid Na + ion conductors have attracted significant interest in recent years, because of their possible application as electrolytes in Na + solid-state batteries. One of the most investigated Na + solid-electrolyte classes is the Na 3 PS 4 material family, because of its relatively high ionic conductivity paired with its structural simplicity and compositional variety, making it a suitable model system for sodium-ion conductors. Upon substitution and doping, room-temperature ionic conductivities ranging from 0.018 mS cm –1 (Na 3 PS 4 ) , to 0.3 mS cm –1 (Na 3 SbSe 4 ) and up to 40 mS cm –1 (W-doped Na 3 SbS 4 ) , have been achieved. As a consequence of its high ionic conductivity, these materials are currently considered as ionic conductors in solid-state battery applications. In part, the fast ionic transport has been explained by largely anharmonic phonon dynamics, ,, and other considerations about atomic vibrations . However, a deeper investigation and understanding of the thermal transport properties, which are fundamentally linked to the lattice dynamics of a material, , are missing.…”
mentioning
confidence: 99%